1988
DOI: 10.1007/bf01962169
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibodies toAspergillus fumigatus catalase in patients with cystic fibrosis

Abstract: Seven to ten percent of patients with cystic fibrosis had serum antibodies to the catalase antigen of Aspergillus fumigatus in three cross-sectional surveys between 1977 and 1984. A total of 208 patients participated at least once, and the cumulated frequency of catalase antibodies in 94 patients included in all three surveys was 16%. The titre range was 1 to 16. The prevalence rate of Aspergillus fumigatus in sputum was 50% for a 2.5-year observation period. Catalase antibodies were strongly associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…In CF, they are usually found in a minority of patients colonised by A. fumigatus [2,32] and their presence in these patients was shown to be related to decreased pulmonary function [32]. In vitro, all the strains of A. fumigatus from CF patients that were tested for catalase activity by a spectrophotometric assay produced varying levels of the enzyme (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…In CF, they are usually found in a minority of patients colonised by A. fumigatus [2,32] and their presence in these patients was shown to be related to decreased pulmonary function [32]. In vitro, all the strains of A. fumigatus from CF patients that were tested for catalase activity by a spectrophotometric assay produced varying levels of the enzyme (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, regarding patients with CF, the detection of anti-A. fumigatus catalase antibodies has been shown to be associated with a clinical or functional deterioration (47). Because of this and considering the high similarity between the biochemical products of A. fumigatus Cat1 and S. boydii catalase A1, we investigated the potential application of catalase A1 for specific antibody detection in CF patients.…”
Section: Discussionmentioning
confidence: 99%
“…At each visit, patients were evaluated clinically and, if old enough to cooperate, the lung function was assessed by spirometry. Microbiological examination of sputum included mycological culture at all times (see below) and most patients were investigated for serum antibodies to A. fumiga tus in 1982 and 1984 as part of cross-sectional studies [4,5]. ABPA was suspected in patients with increased bronchial obstruction, and when clinically indicated the following tests were performed: chest X-ray, count of eosinophils in peripheral blood, total serum IgE, skin-prick test and/or radioallergosorbent test (RAST) with A.fu migatus antigen, and serum precipitins to A.fumigatus.…”
Section: Patientsmentioning
confidence: 99%
“…We have reviewed the medical records of 200 patients attending the Danish CF centre over a 5.5-year period (1982)(1983)(1984)(1985)(1986)(1987) in order to assess the inci dence of ABPA. Moreover, we investigated the diag nostic significance of serum antibodies to the catalase antigen of A.fumigatus, as a previous study at our centre has demonstrated an association between cata lase antibodies, frequent isolation of the fungus from sputum, and slowly deteriorating lung function pa rameters [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation